2014
DOI: 10.1007/s00262-014-1565-4
|View full text |Cite
|
Sign up to set email alerts
|

The microtubule-depolymerizing agent ansamitocin P3 programs dendritic cells toward enhanced anti-tumor immunity

Abstract: In addition to direct tumor cell cytotoxicity, chemotherapy can mediate tumor reduction through immune modulation of the tumor microenvironment to promote anti-tumor immunity. Mature dendritic cells (DCs) play key roles in priming robust immune responses in tumor-bearing hosts. Here, we screened a panel of 21 anticancer agents with defined molecular targets for their ability to induce direct maturation of DCs. We identified ansamitocin P3, a microtubule-depolymerizing agent, as a potent inducer of phenotypic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 49 publications
1
58
1
Order By: Relevance
“…In (Figure 1), which induced dendritic cells in priming robust immune responses in tumor-bearing hosts [17].…”
Section: Discussionmentioning
confidence: 99%
“…In (Figure 1), which induced dendritic cells in priming robust immune responses in tumor-bearing hosts [17].…”
Section: Discussionmentioning
confidence: 99%
“…While summarizing all of these studies here is not possible, we found the following ones to be of particular interest and, in some cases, largely representing the general trends in this field (not mentioned in any particular order): (1) Mitchell et al documented that pre-conditioning the intended site for DC-based vaccination with the tetanus/diphtheria toxoid (acting as a "recall antigen") significantly improves the lymph nodehoming of DCs thereby inducing (CCL3-dependent) anti-glioblastoma immunity following DC-based vaccination in mice and patients; 185 (2) Carreno et al reported that a DC-based vaccine boosts (naturally-occurring) neoantigen-specific antimelanoma immunity (comprising an increase in diversity and clonality of neoantigen-specific T cells) associated with de novo emergence of MHC class I-restricted neoantigens; 186 (3) Garg et al found that next-generation DC-based vaccines relying on immunogenic cell death (ICD) elicited by hypericin-dependent photodynamic therapy (Hyp-PDT) in glioma cells induce potent anti-glioblastoma immunity in an orthotopic murine model (both in prophylactic and curative settings, alone or in combination with chemotherapy), accompanied by a shift from a Tregdominated intracranial immune contexture to a Th1/Th17/ CTLs-dominated one; 187 (4) Ohshio et al observed that targeting immunosuppressive cancer-associated fibroblasts with an anti-fibrotic agent, tranilast, in combination with DC-based vaccination drastically improves (CTL-and NK-cell-driven) antitumor immunity against subcutaneously transplanted lymphomas, lung carcinomas and melanomas; 188 (5) Xiang et al documented that ovalbumin-loaded upconversion nanoparticles (i.e., nanoparticles exhibiting photon upconversion, a process wherein two or more photons of low energy are absorbed and converted into a single emitted photon of higher energy) can be used for antigen loading and maturation of DCs, which can also be tracked in vivo (via luminescence imaging), so that these DCs eventually drive potent ovalbumin-specific immunity; 189 194 and (11) Martin et al discovered that ansamitocin P3, a microtubule depolymerizing agent, enhances DC activation thereby making DC-based vaccines potent inducers of antigen-specific T cells, especially in combination with ICBs targeting programmed cell death 1 (PDCD1, also known as PD-1) and cytotoxic T lymphocyte-associated protein 4 (CTLA4). 195 …”
Section: Recent Preclinical Developmentsmentioning
confidence: 99%
“…Neutrophils were enriched from BM cells using an EasySep mouse neutrophil enrichment kit (StemCell Technologies). BMDCs were generated as previously described .…”
Section: Methodsmentioning
confidence: 99%